Whistle : [large type] a novel - Barclay, Linwood (William Morrow, 2025)
"Annie Blunt has had an unimaginably terrible year. First, her husband was killed in a tragic hit-and-run accident, then one of the children's books she's built her writing and illustrating career on ignited a major scandal. Desperate for a fresh start, she moves with her son Charlie to a charming small town in upstate New York where they can begin to heal. But Annie's year is about to get worse. Bored and lonely in their isolated new surroundings, Charlie is thrilled when he finds a forgotten train set in a locked shed on their property. Annie is glad to see Charlie happy, but there's something unsettling about his new toy. Strange sounds wake Annie in the night--she could swear she hears a train, but there isn't an active track for miles--and bizarre things begin happening in the neighborhood. Worse, Annie can't seem to stop drawing a disturbing new character that has no place in a children's book. Grief can do strange things to the mind, but Annie is beginning to think she's walked out of one nightmare straight into another, only this one is far more terrifying..." --